2019
DOI: 10.1002/cbdv.201800510
|View full text |Cite
|
Sign up to set email alerts
|

Design, Microwave‐Assisted Synthesis and in Vitro Antibacterial and Antifungal Activity of 2,5‐Disubstituted Benzimidazole

Abstract: Seventeen novel 2,5‐disubstituted benzimidazole derivatives were designed, synthesized and evaluated for their antibacterial activities. The tested compounds B1–B4 and C2–C6 exhibited not only good antifungal activity but also favorable broad‐spectrum antibacterial activity. Also, the lowest MIC of antibacterial and antifungal activity was 2 μg/mL and 4 μg/mL, respectively. It suggested that the structure of compound including the different substituent and its sites directly affected the efficacy of the synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…F0414 is a benzimidazole compound with no biological activities reported. There has been a lot of benzimidazole compounds used in clinic, which exhibited various properties, such as anti-tumor, anti-viral, anti-bacterial, anti-fungal, and anti-metabolic syndrome ( He et al, 2019 ; Shi et al, 2019 ; Singh et al, 2019 ; Tharmalingam et al, 2019 ). For example, pracinostat, a novel benzimidazole-based histone deacetylase inhibitor, has been identified as a potential agent for treating breast cancer ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…F0414 is a benzimidazole compound with no biological activities reported. There has been a lot of benzimidazole compounds used in clinic, which exhibited various properties, such as anti-tumor, anti-viral, anti-bacterial, anti-fungal, and anti-metabolic syndrome ( He et al, 2019 ; Shi et al, 2019 ; Singh et al, 2019 ; Tharmalingam et al, 2019 ). For example, pracinostat, a novel benzimidazole-based histone deacetylase inhibitor, has been identified as a potential agent for treating breast cancer ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…2‐(pyridin‐3‐yl)‐1 H ‐benzo[d]imidazole : [61] m=0.327 g. 1 H NMR (400 MHz, DMSO‐ d 6 ) δ (ppm): 13.12 (s, 1H), 9.38 (s, 1H), 8.70 (s, 1H), 8.52 (s, 1H), 7.63 (s, 3H), 7.26 (s, 2H). HRMS (EI): Calcd for C 13 H 9 N 3 [M+H] + 196.0869, found 196.0877.…”
Section: Methodsmentioning
confidence: 99%
“…A wide range of products was obtained in moderate to excellent yields under microwave irradiation. 133 Some synthesized compounds showed strong antibacterial and antifungal activity ( Scheme 64 ). Bioassay study revealed that several synthesized compounds exhibited good antifungal activity and broad-spectrum antibacterial activity.…”
Section: Benzimidazole Synthesis By Condensation Of 12-benzenediamine...mentioning
confidence: 99%